2020
DOI: 10.1016/j.arr.2020.101138
|View full text |Cite
|
Sign up to set email alerts
|

Ozone: a natural bioactive molecule with antioxidant property as potential new strategy in aging and in neurodegenerative disorders

Abstract: Highlights Aging and neurodegenerative diseases are characterized by complex and multifactorial aetiology and challenges regarding treatments efficacy and costs persist. Oxygen-ozone (O 2 -O 3 ) therapy is a non-invasive, non-pharmacological, low cost and no-side effect procedure based on antioxidant capacity of O 3 . A plethora of scientific evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 239 publications
(324 reference statements)
3
68
0
Order By: Relevance
“…Similar results have been obtained in laboratory experiments with animal models of rheumatoid arthritis and psoriasis [282][283][284][285][286][287], and with fibromyalgia [295][296][297][298][299][300][301]. Although data is limited, given the presence of mitochondrial dysfunction, oxidative injury, and inflammation in affected neuronal populations in the neurodegenerative disorders [302][303][304][305], it would seem that these conditions too would be suitable candidates for ozone PC.…”
Section: The Case For Ozonesupporting
confidence: 61%
“…Similar results have been obtained in laboratory experiments with animal models of rheumatoid arthritis and psoriasis [282][283][284][285][286][287], and with fibromyalgia [295][296][297][298][299][300][301]. Although data is limited, given the presence of mitochondrial dysfunction, oxidative injury, and inflammation in affected neuronal populations in the neurodegenerative disorders [302][303][304][305], it would seem that these conditions too would be suitable candidates for ozone PC.…”
Section: The Case For Ozonesupporting
confidence: 61%
“…Moreover, a high dose of O 3 promotes inflammation by the activation of the NF-κB pathway [ 64 ]. Additionally, the inhibition of the NF-κB pathway could potentially downregulate iNOS [ 68 ] because, for bortezomib treatment, it has been described that most of the infiltrating macrophages in the dorsal root ganglia are iNOS-expressing inflammatory macrophages [ 47 ].…”
Section: Modulation Of Oxidative Stress By Ozone Therapymentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37] These properties make ozone a useful medical tool, which can be used as either a disinfectant or an adjuvant agent in the therapy of numerous diseases. 32,[38][39][40] This paradox of ozone effect should be explained by the balance of NF-κB and Nrf2 signaling. Actually, many studies have been reported about the cross-talk between NF-κB and Nrf2, that Nrf2 plays a critical role in counteracting NF-κB driven inflammatory response.…”
Section: Introductionmentioning
confidence: 99%